Potential effect of antimicrobial agents against Staphylococcus aureus and Pseudomonas aeruginosa strains from patients with skin infections - A. Hashim, Intisar; H. Wdaah, Qasim; A. Atya, Ahmed (University of Thi-Qar Journal of Science, 2019)
The present study is designed to investigate S. aureus and Pseudomonas aeruginosa bacteria isolated from wound and burn patients in Thi-qar province and detection of the optimal antibiotic. All S. aureus isolates were tested for their susceptibility to thirteen antibiotics, all S. aureus isolates 100% were resistant to ß-lactam antibiotics to both Ampicillin, penicillin, 91.5% to both cefoxitin, oxacillin, 89.1% to both Vancomycin, ciprofloxacin , iodine and ethanol has reduced 100% the growth of S. aureus and Tobramycin , 78.3% to tetracycline ,67.5% Netilmicin, 64.8% Clindamycin, 59.4% Erythromycin, 45.9% to both Amikacin , Ciprofloxacin and 29.7%Gentamicin while Pseudomonas aeruginosa isolates were tested for their susceptibility to twelve antibiotics, all isolates 100% were resistant to both Trimethoprim , Amikacin, Piperacillin, Ticarcillin, Aztreonam and Gentamicin ,95.2% cefotaxime , 85.7%Colistin sulphate, 80.9% to both Netilmicin, Ceftazidime, 76.1% Ciprofloxacin and 28.5% Imipenem. It concluded from the present study that all isolates of S. aureus were resistant to B-lactam antibiotics and Ciprofloxacin must be the best antibiotic that used against this microorganism.